2023
DOI: 10.1186/s13018-023-04400-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram for predicting new vertebral compression fractures after percutaneous kyphoplasty in postmenopausal patients

Jianhu Zheng,
Yan Gao,
Wenlong Yu
et al.

Abstract: Background Postmenopausal women face a heightened risk of developing new vertebral compression fractures (NVCFs) following percutaneous kyphoplasty (PKP) for osteoporotic vertebral compression fractures (OVCFs). This study aimed to develop and validate a visual nomogram model capable of accurately predicting NVCF occurrence post-PKP to optimize treatment strategies and minimize occurrence. Methods This retrospective study included postmenopausal wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Studies by Ma et al identified female gender, cerebrovascular disease, fracture history, and cement intervertebral leakage as risk factors for NVCF ( 17 ). Zheng et al, in a population of postmenopausal individuals, found cement leakage, poor cement dispersion, and endplate fractures as independent predictors in their model for NVCF ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Ma et al identified female gender, cerebrovascular disease, fracture history, and cement intervertebral leakage as risk factors for NVCF ( 17 ). Zheng et al, in a population of postmenopausal individuals, found cement leakage, poor cement dispersion, and endplate fractures as independent predictors in their model for NVCF ( 44 ).…”
Section: Discussionmentioning
confidence: 99%